Fiscal Deficits and Inflation : A New Look at the Emerging Market Evidence - Terrones, Marco (IMF Working Papers; Working Paper ;, 2001)
Empirical studies have had little success in finding a statistically significant relationship between fiscal deficits and inflation in broad cross-country panels. This paper provides new econometric estimates for a panel of 23 emerging market countries during 1970-2000. Unlike previous studies, we allow for a rich dynamic specification and focus on the long-run relationship between the two variables controlling for differences in the inflation tax base. We find that a 1 percentage point reduction in the ratio of fiscal deficit to GDP typically lowers long-run inflation by 1 1\2 to 6 percentage points, depending on the size of the inflation tax base.